Recent transformations in the high-Arctic glacier landsystem, Ragnarbreen, Svalbard - Ewertowski, Marek (Wiley / © 2014 Swedish Society for Anthropology and Geography, 2014)
Ragnarbreen is a small glacier located in the central part of Spitsbergen Island (Svalbard archipelago) and fed by the larger ice mass of Mittag-Lefflerbreen. Glacier recession and landforms' development in the foreland of Ragnarbreen are quantified using time-series orthophotos and digital elevation models, which were generated based on aerial photographs from 1961 (black and white frame camera), 1990 (false infrared frame camera) and 2009 (colour digital camera), obtained from the Norsk Polar Institute. Receding from its maximum Little Ice Age extent, attained in the period 1900/1920–2013, the glacier margin retreated by 1658 m while the extent of the area of ice decreased by 26%. The glacier snout lost 135 million m3 of ice during the period 1961–2009, whereas landform changes (mainly due to dead-ice melting and debris flow activity) were more than twenty-five times lower, with the less than 5 million m3 of sediment and dead ice volume loss. In terms of landscape alteration between 1961 and 2009, the most important was the creation of a terminoglacial lake, which acted as a sedimentary trap and at the same time probably accelerated glacier retreat. The second most active component was the lateral moraines whose transformations were divided into four phases, with various magnitudes of debris flow and backwasting activity that changed with time. The end moraine complex was the most stable component, affected mainly by dead-ice downwasting and to a lesser extent by sporadic debris flows.
Keywords: ice-cored moraine; Spitsbergen; glacial geomorphology